Epigenetic modification by dietary factors: Implications in metabolic syndrome. (April 2017) - Park, Jae-Ho; Kim, Soon-Hee; Lee, Myeong Soo; Kim, Myung-Sunny
Abstract: Dietary factors play a role in normal biological processes and are involved in the regulation of pathological progression over a lifetime. Evidence has emerged indicating that dietary factor-dependent epigenetic modifications can significantly affect genome stability and the expression of mRNA and proteins, which are involved in metabolic dysfunction. Since metabolic syndrome is a progressive phenotype characterized by insulin resistance, obesity, hypertension, dyslipidemia, or type 2 diabetes, gene-diet interactions are important processes involved in the initiation of particular symptoms of metabolic syndrome and their progression. Some epigenetic risk markers can be initiated or reversed by diet and environmental factors. In this review, we discuss recent advances in our understanding of the interactions between dietary factors and epigenetic changes in metabolic syndrome. We discuss the contribution of nutritional factors in transgenerational inheritance of epigenetic markers and summarize the current knowledge of epigenetic modifications by dietary bioactive components in metabolic diseases. The intake of dietary components that regulate epigenetic modifications can provide significant health effects and, as an epigenetic diet, may prevent various pathological processes in the development of metabolic disease.